The relationship between neonatal stress in preterm infants and developmental outcomes at the corrected age of 24–30 months - Pavlyshyn, Halyna; Sarapuk, Iryna; Kozak, Kateryna (Frontiers in Psychology, 2024)
The aim of research was to study the relationship between the stress experienced by preterm infants in the neonatal intensive care unit (NICU) and developmental status in the follow up, and to establish factors, associated with their neurodevelopment. Methods. The first stage of research involved measuring stress markers (cortisol, melatonin) in infants (n=56) during their NICU stay; the second phase assessed the developmental status at the corrected age of 24-30 months. Results. The total ASQ-3 score, communication, problem solving, and personal-social skills scores at the corrected age of 24-30 months were positively correlated with melatonin level determined in the neonatal period (r=0.31, p=0.026; r=0.36, p=0.009; r=0.30, p=0.033, and r=0.32; p=0.022 respectively). In the same time, ASQ-3 communication and personal-social scores were negatively correlated with cortisol level (r=-0.31, p=0.043; r=-0.35, p=0.022). The ROC-curve analysis revealed that a decrease of melatonin below 3.44 ng/ml and 3.71 ng/ml during the neonatal period could predict communication and problem-solving delay respectively. An increase in cortisol above 0.64 mcg/dl is predictive in personal-social delay.Negative correlation was identified between the NICU and total hospital stay duration and ASQ-3 communication scores in the follow-up (r=-0.27; p=0.049 and r=-0.41; p=0.002, respectively).The duration of mechanical ventilation was negatively correlated with gross motor scores (r=-0.46; p=0.043). Apgar score was positively correlated with ASQ-3 communication (r=0.29; p=0.032) and personal-social scores (r=0.28; p=0.034); maternal agewith ASQ-3 total (r=0.29; p=0.034), communication (r=0.37; p=0.006), and personal-social scores (r=0.29; p=0.041). Positive correlations were observed between gestational age and communication scores (r=0.28; p=0.033).Infants who suffered neonatal sepsis had significantly often delay of communication (p=0.014) and gross motor skills (p=0.016). Children who required mechanical ventilation were more likely to have communication delay (p=0.034). Conclusions. Developmental outcomes in preterm infants at the corrected age of 24-30 months were associated with neonatal stress. Correlations between the communication, problem-solving and personal-social development in the follow up and cortisol and melatonin levels determined in the neonatal period supported this evidence. Factors as low gestational age, duration of hospital and NICU stay, mechanical ventilation, and sepsis were associated with more frequent delays in communication, gross motor and problems-solving skills.